UNDERSTANDING BARRIERS TO THE DEVELOPMENT OF KOREAN LISTENING SKILLS AMONG UNIVERSITY STUDENTS - Fitra Jasmine Adefiannisa; Salismi Zulfi Maulidita; Oboy Oboy (Jurnal Multidisipliner Bharasumba, 2025)
The growing influence of the Korean Wave has significantly increased interest in learning the Korean language in Indonesia. However, many learners continue to face notable challenges in mastering Korean listening skills. This study investigates the specific difficulties encountered by beginner-level learners using a qualitative exploratory design. Data were collected through a questionnaire completed by 16 students and in-depth interviews with five selected participants. The findings reveal five major barriers: difficulty processing fast speech, limited comprehension of unfamiliar topics, challenges in recognizing accents and pronunciation variations, heavy reliance on visual or textual support, and struggles with vocabulary retention. These difficulties indicate that listening comprehension is a multifaceted skill requiring more than exposure to Korean media. The study concludes that targeted instructional strategies are essential to strengthen phonological awareness, vocabulary mastery, and independent listening skills among Korean learners in Indonesia.